Public Management - Villoria Mendieta, Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The text analyzes the concept of public management. It begins with the explanation of its origins and differences with other approaches, it also explains its object of study, the subject of reference to which it is addressed and the methodology and epistemology of this branch or approach of public administration studies.